Laboratory assessment of shear strength parameters of sand amended via subsequent biopolymer-based soil treatment and enzyme-induced calcite precipitation combinations - Park, Suhyuk; Park, Jinwoo; Chang, Ilhan (IOP Conference Series: Earth and Environmental Science, 2024)
Current ground improvement practices predominantly rely on cement; however, interest in strengthening the ground in an environmentally sustainable manner is growing due to concerns regarding the environmental impact, such as the high CO2 footprint associated with cement usage. Biopolymer-based soil treatment (BPST) and enzyme-induced calcite precipitation (EICP) have emerged as promising methods for environmentally friendly ground improvement. While several studies have demonstrated the effectiveness of BPST and EICP individually, both methods have their limitations, which can be seen as complementary (for instance, EICP is more effective for coarse soils, whereas BPST is more effective for clayey soils). Recently, efforts have been made to combine BPST with EICP to address these limitations. This study considered four consecutive BPST-EICP combinations: 1) EICP alone, 2) BPST alone, 3) pre-EICP followed by post-BPST, and 4) pre-BPST followed by post-EICP. Laboratory experiments were conducted to assess the shear strength parameters (i.e., direct shear cohesion and friction angle) of sand treated using these four methods. The peak and residual shear strength parameters of the pre-EICP followed by post-BPST soil were the highest among all cases. However, each combination is suited to specific site conditions, such as soil type, groundwater conditions, and the purpose of ground improvement.